2017
DOI: 10.3389/fncel.2017.00237
|View full text |Cite
|
Sign up to set email alerts
|

Differential Peripheral Proteomic Biosignature of Fluoxetine Response in a Mouse Model of Anxiety/Depression

Abstract: The incorporation of peripheral biomarkers in the treatment of major depressive disorders (MDD) could improve the efficiency of treatments and increase remission rate. Peripheral blood mononuclear cells (PBMCs) represent an attractive biological substrate allowing the identification of a drug response signature. Using a proteomic approach with high-resolution mass spectrometry, the present study aimed to identify a biosignature of antidepressant response (fluoxetine, a Selective Serotonin Reuptake Inhibitor) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 59 publications
5
26
0
Order By: Relevance
“…Föcking, M et al found that AP2B1 was up‐regulated in the brain regions of patients with schizophrenia (Focking et al, ). It is worth mentioning that AP2B1 is up‐regulated in a mouse model of anxiety/depression and associated with antidepressant drug response (Mendez‐David et al, ). In this study, AP2B1 was down‐regulated in the blood of MDD and the expression pattern was validated by qRT‐PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Föcking, M et al found that AP2B1 was up‐regulated in the brain regions of patients with schizophrenia (Focking et al, ). It is worth mentioning that AP2B1 is up‐regulated in a mouse model of anxiety/depression and associated with antidepressant drug response (Mendez‐David et al, ). In this study, AP2B1 was down‐regulated in the blood of MDD and the expression pattern was validated by qRT‐PCR.…”
Section: Discussionmentioning
confidence: 99%
“…While these data are consistent with a decreased hedonic drive, they may also have resulted from anxiety-induced suppression of feeding ( 84 ). In fact, a recent study shows that administration of anxiolytic drug fluoxetine results in a recovery of feeding behavior in a corticosterone-induced rodent model of anxiety ( 85 ). Future studies of GEPR-3s investigating changes in reward and learning behaviors under conditions of similarly reduced anxiety and/or in the presence of anxiolytic drugs may help to parse these effects.…”
Section: Discussionmentioning
confidence: 99%
“…To simulate the HPA dysregulation seen in the genetic and stress-based models of depression, researchers have used exogeneous corticosterone administration in rodents (160). Robust and highly reproducible anxiety-and depression-like behaviors have been reported following chronic oral administration of corticosterone, which may or may not lead to an elevation in the level of serum corticosterone (133,(161)(162)(163)(164)(165)(166)(167)(168)(169). In addition to the behavioral changes, chronic exogeneous corticosterone is associated with several neurobiological changes seen in MDD models including the disruption of adult hippocampal neurogenesis (170), and decreased hippocampal brain derived neurotrophic factor (BDNF) (171).…”
Section: Modelling Depression Using Exogeneous Corticosterone Adminismentioning
confidence: 99%